Digitising Hardware Shop Management to Enhance Business Operation - Ong, Jian Yao; Mohmad Hassim, Yana Mazwin (Applied Information Technology And Computer Science, 2022)
Rong Fatt hardware shop is a local hardware shop located in Batu Pahat, Johor that sells various type of hardware such as PVC pipe, screwdriver, wrench, hinge and plywood to the customers. The purpose of this final year project is to develop a web based inventory management system for Rong Fatt hardware shop. The hardware shop is currently facing some problem as the shop is still using logbooks to manually record the all the stocks and transactions. This method is quite inefficient as it takes up a lot of time to complete all the manual recording. Several modules such as product information, stock managing, report generating, register, login, and notification are introduced for the system. Waterfall model is used as the software development method for this project. The system will be built using Visual Studio Code text editor and MySQL is used for database system. To design a complete system, the functional requirement, non-functional requirement and user requirement are well elicited and defined from the stakeholders. The system analysis is illustrated through Context Diagram, Data Flow Diagram and Entity Relationship Diagram. Last, interface design and data dictionary of the system are also included in system design subtopic. Through this system, Rong Fatt hardware shop to manage stocks in a more organised way and place orders on supplier easier. The development of this system will assist Rong Fatt hardware shop in daily business operation and helping them getting familiar with computerize inventory system.